2016
DOI: 10.1063/1.4939286
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt (II) oxide and nickel (II) oxide alloys as potential intermediate-band semiconductors: A theoretical study

Abstract: Solar cells based on single pn junctions, employing single-gap semiconductors can ideally achieve efficiencies as high as 34%. Developing solar cells based on intermediate-band semiconductors (IBSCs), which can absorb light across multiple band gaps, is a possible way to defy this theoretical limit and achieve efficiencies as high as 60%. Here, we use first principles quantum mechanics methods and introduce CoO and Co0.25Ni0.75O as possible IBSCs. We show that the conduction band in both of these materials is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 43 publications
4
34
0
Order By: Relevance
“…25 For the exchange-correlation functional, we tested both the local density approximation (LDA) 26 and the generalized gradient approximation (GGA) of Perdew-Burke-Ernzerhof (PBE). 27 We found that LDA describes the electronic structure of CoO as a semiconductor better than GGA-PBE, in agreement with previous studies 28 and results reported here are from LDA calculations only. In order to account for the on-site repulsion between d electrons, DFT+U within Dudarev's approach was adopted with U-J parameter values of 4 and 7 for Co and Ni, respectively.…”
Section: Theoretical Calculationssupporting
confidence: 92%
“…25 For the exchange-correlation functional, we tested both the local density approximation (LDA) 26 and the generalized gradient approximation (GGA) of Perdew-Burke-Ernzerhof (PBE). 27 We found that LDA describes the electronic structure of CoO as a semiconductor better than GGA-PBE, in agreement with previous studies 28 and results reported here are from LDA calculations only. In order to account for the on-site repulsion between d electrons, DFT+U within Dudarev's approach was adopted with U-J parameter values of 4 and 7 for Co and Ni, respectively.…”
Section: Theoretical Calculationssupporting
confidence: 92%
“…to test the transferability of SCAN+UMn calculations. Also, previous work 25,26,92 has demonstrated the relative insensitivity in energy and band-gap trends for variations of ±0.5 eV in the magnitude of U used. The text annotations in each panel of Figure 3, along the dashed lines, indicate the ideal U value that minimizes the absolute error between SCAN+U and experimental enthalpies for the corresponding oxidation reaction.…”
Section: Formation Energies Of Main Group Oxidesmentioning
confidence: 90%
“…A plane wave cutoff energy of 520 eV was applied in our calculations. Due to insufficient consideration of the on-site Columbic repulsion, between Co d electrons, the GGA + U approach was used with U−J = 4.0 for the Co atoms 54,55 .…”
Section: Methodsmentioning
confidence: 99%